PENGEMBANGAN LEARNING MANAGEMENT SYSTEM BERBASIS MOODLE PADA MATA PELAJARAN DASAR-DASAR TEKNIK KOMPUTER JARINGAN DAN TELEKOMUNIKASI - Putri, Novia Diada Eka; Rini, Faiza; Alfiriani, Adlia (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
The purpose of this study was to produce a Learning Management System (LMS) on valid class X TKJ business process material. To produce a Moodle-based Learning Management System (LMS) on business process material for grade X TKJ which is practical. This research method uses the Research and Development (R&D) method with the ADDIE development model. The subjects of this study consisted of 3 media validation people, 3 material validity people, 1 teacher practicality person and 68 student practicality people. The results of this study showed the average value of the media validation test by the validator of 83.93% with a very valid category while the material validation was 77.96% with a very valid category. The teacher's practicality test was 88.54% with a very practical category, while the practicality of students in class X TKJ 1 was obtained at 82.03% and TKJ 2 students obtained an average of 84.56 with a very practical category. Learning Management System (LMS) is feasible to use as learning. improving the quality of learning, with the use of media that is more interactive and efficient for teachers and students, and able to eliminate student fatigue.